A Novel Study and Meta-Analysis of the Genetic Variation of the Serotonin Transporter Promoter in the Italian Population Do Not Support a Large Effect on Alzheimer's Disease Risk. (2nd June 2011) - Polito, Letizia; Prato, Francesca; Rodilossi, Serena; Ateri, Eleonora; Galimberti, Daniela; Scarpini, Elio; Clerici, Francesca; Mariani, Claudio; Forloni, Gianluigi; Albani, Diego
Abstract : Alzheimer's disease (AD) is a neurodegenerative disorder whose clinical onset is mainly characterized by memory loss. During AD progression, behavioral and psychological symptoms of dementia (BPSD) frequently occur. In this paper we evaluated the association between AD and the short/long (S/L) functional polymorphism of the promoter region of the 5-hydroxytryptamine (5-HT) transporter gene ( SLC6A4 ). The S-allele shows a 2-fold reduced transcriptional rate, causing an imbalance in 5-HT intracellular availability that might in turn trigger behavioral and cognitive alterations. We also genotyped the SLC6A4 promoter functional variant rs25531 (A → G ). By comparing the genotypic and allelic frequencies in an Italian population of 235 AD and 207 controls, we found an association between 5-HTTLPR and AD (odds ratio for the L-allele versus the S-allele: 0.74, associated P value = .03), while no difference was found for the rs25531 . A meta-analysis of studies in Italy assessing 5-HTTLPR and AD risk gave an estimation of odds ratio for the L-allele versus the S-allele of 0.85 (associated P value = .08). Overall, our findings are not supportive of a large genetic effect of the explored polymorphisms on AD risk.